Knowledge and understanding of obstetric danger signs among pregnant women attending the antenatal clinic at the National Referral Hospital in Thimphu, Bhutan: a cross-sectional study - Saran Tenzin Tamang; Thinley Dorji; Sonam Yoezer; Thinley Phuntsho; Phurb Dorji (BMC, 2021)
Abstract Background The third Sustainable Development Goal for 2030 development agenda aims to reduce maternal and newborn deaths. Pregnant women's understanding of danger signs is an important factor in seeking timely care during emergencies. We assessed knowledge of obstetric danger signs using both recall and understanding of appropriate action required during obstetric emergencies. Methods This was a cross-sectional study among pregnant women attending antenatal clinic at Bhutan's largest hospital in Thimphu. Recall was assessed against seven obstetric danger signs outlined in the Mother and Child Health Handbook (7 points). Understanding of danger signs was tested using 13 multiple choice questions (13 points). Knowledge was scored out of 20 points and reported as 'good' (≥80%), 'satisfactory' (60-79%) and 'poor' (< 60%). Correlation between participant characteristics and knowledge score as well as number of danger signs recalled was tested using Pearson's correlation coefficient. Association between knowledge score and participant characteristics was tested using t-tests (and Kruskal-Wallis test) for numeric variables. Socio-demographic and clinical characteristics associated with the level of knowledge ('good' versus 'satisfactory' and 'poor' combined) were assessed with odds ratios using a log-binomial regression model. All results with p < 0.05 were considered significant. Results Four hundred and twenty-two women responded to the survey (response rate = 96.0%). Mean (±SD) knowledge score was 12 (±2.5). Twenty women (4.7%) had 'good' knowledge, 245 (58.1%) had 'satisfactory' knowledge and 157 (37.2%) had 'poor' knowledge. The median number of danger signs recalled was 2 (IQR 1, 3) while 68 women (20.3%) could not recall any danger signs. Most women were knowledgeable about pre-labour rupture of membranes (96.0%) while very few women were knowledgeable about spotting during pregnancy (19.9%). Both knowledge score and number of danger signs recalled had significant correlation with the period of gestation. Women with previous surgery on the reproductive tract had higher odds of having 'good' level of knowledge. Conclusions Most pregnant women had 'satisfactory' knowledge score with poor explicit recall of danger signs. However, women recognized obstetric emergencies and identified the appropriate action warranted.